Some features of two-photon absorption in static electric field - Griban, V.M.; Melnichuk, O.V.; Ovander, L.M.; Venger, E.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
We considered the effect of static uniform electric field on the process of two-photon excitonic absorption of light in crystals. The matrix element that determines the above process was calculated using a linear (in the photon field) operator of the electron-photon interaction within the framework of polariton theory. It involves a term that depends on the electric field strength. Using the group theory considerations, we obtained that , at definite orientations of the electric field and polarization vectors, two-photon absorption may occur due to the electric field effect only. The process probability depends also on both the crystal symmetry class and type of an excitonic state. Some special cases are considered in more detail. These are provided by the tables of angular dependencies of process probability, which enables one to experimentally check the results obtained.